A primer of modern art. - Cheney, Sheldon, 1886-1980. (New York, Tudor Publishing Company, 1945)
"A Primer of Modern Art" by Sheldon Cheney is a comprehensive introduction to the movements, styles, and key figures in modern art from the late 19th century to the early 20th century. Cheney aims to demystify modern art by outlining its evolution, major themes, and the socio-political context in which it developed. The book covers various movements such as Impressionism, Expressionism, Cubism, Surrealism, and Abstract Art, explaining the characteristics that define each and the impact they have had on both art and society. Cheney also highlights significant artists and their contributions, providing insightful commentary on their works and philosophies.
"Note on bibliograhies":p. 382
Keywords: Art -- History; surrealism -- Impressionism (Art); Cubism -- Sculpture,Theatre; Mobile Color -- Futurism -- Abstraction; Art, Modern -- 20th century -- History